ANALISIS PENGARUH JUMLAH PENDUDUK, INDEKS PEMBANGUNAN MANUSIA DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP KEMISKINAN DI PROVINSI RIAU TAHUN 2002-2021 - Lapeti Peti Sari; Nurjannah Nurjannah; Indri Yovita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Research this aim for knowing influence variable total population , index development human , and level unemployment open to poverty in Riau Province in 2002-2021. Method analysis in study this using secondary data that is classified as time series data that is descriptive and quantitative . Technique deep data analysis study this use multiple linear regression model estimation with test statistics ( t test, F test , coefficient determination R 2 , coefficient correlation ), and test assumption classic . Results study with test to coefficient regression by partial ( t test ) shows that variable free total population with probability of (0.0430 <0.05) means take effect by significant to poverty in Riau Province. Whereas HDI variable and level unemployment open no take effect by significant to poverty in Riau Province . F test shows that by together third variable total population , HDI and TPT have an effect significant to poverty in Riau Province with prob (F-statistic) of 0.000158 < 0.05 and R2 _ by 65.15%.